The Influence of CAR, FDR, NOM and TPF on Murabahah Financing at Sharia Banks BUKU 3 of 2020 with NPF as Moderating Variable - Mas'ud, Riduan; Fachrozi, Fachrozi; Aminy, Muhammad Muhajir; Wani, Athar Shahbaz (Universitas Islam Negeri Raden Intan Lampung, 2021)
This study aims to examine murabahah financing influenced by credit adequacy ratio, financing to deposit ratio, net operating margin and third party funds with non performing finance as a moderating variable at BUKU 3 sharia commercial banks in 2020. Method used is quantitative associative and data analysis technique using moderated regression analysis with SPSS version 25 tool which contains PROCESS 3.1 macro syntax. The population in this study is Sharia Commercial Banks included in the BUKU 3 category so that a sample of 4 banks is obtained; Bank Syariah Mandiri, BNI Syariah, BRI Syariah and BTPN Syariah. The effect of credit adequacy ratio through murabahah financing on non performing finance shows that non performing finance has no effect as a moderating variable affecting credit adequacy ratio through murabahah financing, financing to deposit ratio through murabahah financing on non performing finance shows that non performing finance has an effect as a moderating variable affecting financing to deposit ratio through murabahah financing, the effect of net operating margin through murabahah financing on non performing finance shows that non performing finance influential as a moderating variable affecting net operating margin through murabahah financing, the effect of third party funds through murabahah financing on non performing finance shows that non performing finance has an effect as a moderating variable affecting third party funds through murabahah financing.